2022
DOI: 10.3390/jcm11247281
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with RANTES, EMMPIRIN, MMP2 and MMP9, and the Association of These Biomarkers with Cardiovascular Disease in a Multi-Ethnic Population

Abstract: Background: The growing cardiovascular disease (CVD) epidemic calls for further research to identify novel biomarkers for earlier detection and as potential therapeutic targets. Biomarkers Regulated on Activation, Normal T Cell Expressed and Secreted (RANTES), extracellular matrix metalloproteinase inducer (EMMPRIN), and matrix metalloproteinases (MMP-2, and MMP-9) are linked to proatherogenic and proinflammatory pathways of CVD development, the majority of which are coronary artery disease (CAD) and stroke. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Previous studies have also demonstrated the association between these genes and cerebral stroke. For example, MMP9, TLR2, and TIMP1 are related to proinflammatory pathways following stroke [35][36][37] and inducing PTEN degradation can attenuate cerebral stroke [38]. Our data also revealed that age and sex can affect the diagnosis of stroke.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have also demonstrated the association between these genes and cerebral stroke. For example, MMP9, TLR2, and TIMP1 are related to proinflammatory pathways following stroke [35][36][37] and inducing PTEN degradation can attenuate cerebral stroke [38]. Our data also revealed that age and sex can affect the diagnosis of stroke.…”
Section: Discussionmentioning
confidence: 51%
“…MMP9 (Matrix Metalloproteinase 9) levels are believed to increase inflammation and vascular wall degradation, resulting in increased arterial rigidity and a potential increased risk of hypertension and other cardiovascular diseases. However, in a recent clinical study involving 290 patients with CVD and 290 normal subjects, serum MMP9 levels were associated with ethnicity and C‐protein hypersensitivity, but not with coronary artery disease 52 . The study conducted by Lago J et al.…”
Section: Discussionmentioning
confidence: 97%
“…However, in a recent clinical study involving 290 patients with CVD and 290 normal subjects, serum MMP9 levels were associated with ethnicity and C-protein hypersensitivity, but not with coronary artery disease. 52 The study conducted by Lago J et al revealed that the upregulation of MMP9 in response to UVB stimulation contributes to skin aging, thereby indicating a significant association between MMP9 and the aging process. 53 The association between MMP9 and age was further validated through our analysis stratified by age.…”
Section: Discussionmentioning
confidence: 99%